PENGARUH KESIAPAN BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR MATA PELAJARAN IPS SISWA KELAS VIII SMP SWASTA NUSANTARA BALIMBINGAN TANAH JAWA - Sarah Bakdasia Nainggolan; Binsar Tison Gultom; Paulina Herlina N. Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to obtain knowledge about the influence of learning readiness and school environment on the learning outcomes of social studies subjects of grade VIII students of Nusantara Balimbingan Private Junior High School, Java.This type of research is a descriptive quantitative research with a research population of 75 grade VIII students at Nusantara Balimbingan Private Junior High School, Tanah Java and the sample used is all students who are the research population. The sampling technique used is Non Probability Sampling. Data collection techniques are carried out through observation and questionnaires (questionnaires). The hypothesis data collection technique uses multiple regression analysis, partial test (t), simultaneous test (f) and determination coefficient (R²).The results of the study stated that: 1) There was a positive influence between learning readiness on student learning outcomes as seen from the t-test where the t-value of learning readiness (11.335) > ttable value (1.993). 2) There is a positive influence between the school environment on student learning outcomes, this result is seen in the t-test where the t-calculated value of the school environment (4.105) > the ttable value (1.993) which means that there is an influence on these variables. 3) Learning readiness and school environment together affect learning outcomes, this result can be seen in the f test where the fcal value (72.070) > the ftable value (3.12). The R Square determination coefficient test is known to be 0.667, which means that 66.7% of the variables of learning readiness and school environment have an influence on learning outcomes in social studies subjects of grade VIII students of SMP Private Nusantara Balimbingan Tanah Java. While 33.3% is the influence of other variables that were not studied in this study.Based on the results of the study, it can be concluded that learning readiness and school environment have a positive and together effect on the learning outcomes of social studies subjects of grade VIII students of Nusantara Balimbingan Private Junior High School in Java.